Optimal Fiscal Policy in an Economy Facing Socio-Political Instability - Quan Le (Claremont McKenna College, Department of Economics, 2000)
We present a model of optimal government policy when policies may exacerbate socio-political instability (SPI). We show that the optimal policy that takes into account SPI transforms a standard concave growth model into a model with both a poverty trap and endogenous growth. The predictions of the model are tested by developing three new measures of SPI for a panel of 58 countries. Estimating the optimal government policy from the model reveals strong support for the theory. In particular, we show via simulations that optimal policy causes the economy to expand on a quasi-balanced growth path, with the level of SPI determining whether growth is positive or negative.
Keywords: P16; E62; O40; 330; socio-political instability; endogenous growth; public investment; political economy of growth